Man is created to love - Omer, Spahic (www.islamicity.org, 2019)
Life is all about relationships. Man is created as a social being inclined towards knowing and forging bonds and friendships with others. Hence, the Arabic word “insan”, which means “human being, person and man”, is derived from the verb “anisa” which means to be “affable”, “sociable” and “friendly”. Moreover, man is created as Allah’s vicegerent on earth. As such, every animate and inanimate creation has been subjected to him and his services in order to facilitate the execution of his noble terrestrial mission. Man thus naturally forms amiable and productive relationships with his surroundings. In fact, the quality of his stay on earth, as well as the implementation of his vicegerency mission, depends exclusively on the quality of the relationships in question. That also is the only valid measure of the quality -- or otherwise -- of his cultural and civilizational legacies. As a result, man develops a variety of feelings, states and attitudes towards things and beings. They range from personal attachments to strong attractions, and from interpersonal affections to outright pleasures. Such feelings, states and attitudes can likewise morph into a virtue, signifying kindness and compassion, which, in turn, translate itself into a wide range of behavioural patterns towards fellow humans, animals and nature. All those sentiments and moods are intrinsic to man and his primordial nature. However, consistent with his life purpose and design, man prefers and cultivates certain relationships more than others, and favours as well as fosters certain sentiments and moods over others. It is here that true love begins.